2012
DOI: 10.1144/1354-079311-016
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation of CO 2 breakthrough and flow mechanisms in shale

Abstract: Supercritical CO 2 breakthrough and flow mechanisms in shale have been investigated in laboratory experiments using a high pressure flow cell and cylindrical samples of shale from the Draupne formation in the North Sea. The main objective is to study the basic mechanisms involved in the breakthrough process and define the controlling parameters for supercritical CO 2 flow in a low permeable shale.Experimental testing provides new insight into the CO 2 breakthrough process through simultaneous measurements of d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
41
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(41 citation statements)
references
References 17 publications
0
41
0
Order By: Relevance
“…8) is of the type commonly observed in uniaxial loaded, fractured rocks (i.e. irreversible, but closely recoverable -David et al, 2012;Jaeger et al, 2007;Walsh, 1965), but also in the case of isostatic loading of anisotropic rocks (see Skurtveit et al, 2012 for a North Sea shale sample exposed to brine). Furthermore, a comparison of the magnitude of apparent bulk moduli obtained here with the bulk moduli obtained through ultrasonic velocity measurements (Morcote et al, 2010;Schuyer et al, 1954) yield relatively low values both in the evacuated and fluid-equilibrated states.…”
Section: Strain Recoverability Prosper Haniel Coalmentioning
confidence: 71%
“…8) is of the type commonly observed in uniaxial loaded, fractured rocks (i.e. irreversible, but closely recoverable -David et al, 2012;Jaeger et al, 2007;Walsh, 1965), but also in the case of isostatic loading of anisotropic rocks (see Skurtveit et al, 2012 for a North Sea shale sample exposed to brine). Furthermore, a comparison of the magnitude of apparent bulk moduli obtained here with the bulk moduli obtained through ultrasonic velocity measurements (Morcote et al, 2010;Schuyer et al, 1954) yield relatively low values both in the evacuated and fluid-equilibrated states.…”
Section: Strain Recoverability Prosper Haniel Coalmentioning
confidence: 71%
“…Caprock integrity studies from a number of North Sea hydrocarbon fields (Angeli et al, 2009;Harrington et al, 2009;Skurtveit et al, 2010Skurtveit et al, , 2012 indicate dilatancy may be a common mechanism associated with caprock failure. Laboratory experiments injecting carbon dioxide through samples of Draupne shale show a clear increase in volume during gas flow (Angeli et al, 2009;Skurtveit et al, 2010Skurtveit et al, , 2012. Simultaneous measurements of P and S wave acoustic velocity show a change in behaviour as CO 2 moves through the sample, and is related to mechanical changes in the sample.…”
Section: Evidence For Dilatancy Controlled Gas Flowmentioning
confidence: 99%
“…The focus of carbon capture and storage (CCS) studies is on the analysis of the longterm sealing efficiency of lithologies above depleted reservoirs or saline aquifers, typically at larger depths (hundreds to thousands of meters). During the last decade, several studies were published on the sealing integrity of clay-rocks to carbon dioxide (Hildenbrand et al, 2004;Li et al, 2005;Hangx et al, 2009;Harrington et al, 2009;Skurtveit et al, 2012;AmannHildenbrand et al, 2013). In the context of petroleum system analysis, a significant volume of research has been undertaken regarding gas/oil expulsion mechanisms from sources rocks during burial history (Tissot & Pellet, 1971;Appold & Nunn, 2002), secondary migration (Luo et al, 2008) and the capillary sealing capacity of caprocks overlying natural gas accumulations (Berg, 1975;Schowalter, 1979;Krooss, 1992;Schlömer and Kross, 2004;Li et al, 2005;Berne et al, 2010).…”
mentioning
confidence: 99%
“…Chen et al [14] microscopically observed the induced fractures of granite, further confirming that the viscosity of the fracturing fluid affects the fracture propagation, and that the fracture induced by SCO 2 has more branches along the fracture than a fracture produced by freshwater and viscous oil. Skurtveit et al [15] investigated the SCO 2 breakthrough and the flow mechanisms in shale. They discovered that the pressure-induced micro-fractures that occurred during the breakthrough process, in addition to the capillary displacement, are important flow mechanisms.…”
Section: Introductionmentioning
confidence: 99%